METODE HIPNOTERAPI DALAM MERUBAH PERILAKU - Ashadi Cahyadi (Institut Agama Islam Negeri Bengkulu, 2017)
As social beings every human being needs help overcoming the difficulties he encounters so that emerges bebagai form of ministry of the soul, from the mild, moderate to severe (therapy). As a result of the accumulation of problems in human beings, it will give birth psychic burden in life. Then humans feel uneasy, anxious, uncomfortable, frustrated, stressed, and depressed, then people try to get out of the problem trap is one method that can be developed in overcoming various problems of life one of them with hypnotherapy methods that certainly have various levels. many benefits that can be obtained by using this hypnosis-based technique at least the presence of this method is a solution in overcoming human problems for the future in the future.